Probing into emission mechanisms of GRB 190530A using time-resolved spectra and polarization studies: synchrotron origin?. Issue 2 (8th January 2022) - Gupta, Rahul; Gupta, S; Chattopadhyay, T; Lipunov, V; Castro-Tirado, A J; Bhattacharya, D; Pandey, S B; Oates, S R; Kumar, Amit; Hu, Y-D; Valeev, A F; Minaev, P Yu; et al.
ABSTRACT: Multipulsed GRB 190530A, detected by the Gamma-ray Burst Monitor (GBM) and Large Area Telescope onboard Fermi, is the sixth most fluent GBM burst detected so far. This paper presents the timing, spectral, and polarimetric analysis of the prompt emission observed using AstroSat and Fermi to provide insight into the prompt emission radiation mechanisms. The time-integrated spectrum shows conclusive proof of two breaks due to peak energy and a second lower energy break. Time-integrated (55.43 ± 21.30 per cent) as well as time-resolved polarization measurements, made by the Cadmium Zinc Telluride Imager (CZTI) onboard AstroSat, show a hint of high degree of polarization. The presence of a hint of high degree of polarization and the values of low energy spectral index (αpt ) do not run over the synchrotron limit for the first two pulses, supporting the synchrotron origin in an ordered magnetic field. However, during the third pulse, αpt exceeds the synchrotron line of death in few bins, and a thermal signature along with the synchrotron component in the time-resolved spectra is observed. Furthermore, we also report the earliest optical observations constraining afterglow polarization using the MASTER ( P < 1.3  per cent) and the redshift measurement ( z  = 0.9386) obtained with the 10.4 m GTC (Gran Telescopio Canarias) telescopes. The broad-band afterglow can be described with a forward shock model for an ISM (interstellar medium)-like medium with a wide jet opening angle. We determine a circumburst density of n 0 ∼ 7.41, kinetic energy E K ∼ 7.24 × 10 54 erg, and radiated gamma-ray energy E γ, iso ∼ 6.05 × 10 54 erg.